Efeito de antiagregantes plaquetários sobre desfechos clínicos de pacientes com doença arterial periférica: uma revisão sistemática - Mello, Sérgio Luis de (2023)
Introduction: Systematic review study for observation of the effects of antiaggregant drugs, in patients with peripheral arterial disease. Purpose: The benefits and adverse effects from the use of antiaggregant platelet clinical outcomes of the Arterial Disease Peripheral Disease still generates many doubts and controversies. This matter is considered relevant and must be systematically investigated. Methods: A Systematic Review was performed following the “Joanna Briggs Institute” protocol. The review is registered in the International Prospective Register of Systematic Reviews database, under the protocol number CRD42018083466, and was carried out in seven phases, including the high sensitivity search and methodological quality assessment using the JBI Critical Appraisal checklist tool, recommended in the protocol used. Results: The evaluation of the methodological quality of the articles indicated that all of them obtained a score of 12, out of a total of 13 possible points. The increments of walking distance with pain improvement were significant in six studies, in which ticlopidine, picotamide and cilostazol were evaluated. Detailed information regarding the evolution of leg and foot ulcers was not obtained in any of the studies. Reports on quantitative data regarding the performance of amputations were collected in two studies, but statistically rigorous analyzes were not carried out in them. The major outcomes, myocardial infarction, stroke and mortality, were systematically analyzed in three studies, with demonstration of risk reduction when ticagrelor and clopidogrel were used. The presence of bleeding was evaluated in two studies, but the data were not consistent, with heterogeneity of information. Only one study presented quantitative data regarding the bleeding event, referring to no significant difference in dual antiplatelet therapy. Only three studies tested dual antiplatelet therapy using the combination of ticagrelor/aspirin vs. placebo/aspirin; ticagrelor/aspirin vs. clopidogrel/aspirin; ticagrelor/aspirin vs. placebo/aspirin, respectively. These studies demonstrated a significant reduction in ischemic events with the clopidogrel and aspirin treatment strategy versus placebo and aspirin. One of the studies demonstrated a moderate increase in bleeding not considered serious with the combination therapy. Another study showed a consistent increase in bleeding events. Conclusion: The use of platelet antiaggregation therapy in peripheral arterial disease increased the distance of walking with reduction from the episodes of pain. The results referring to appearance or worse ulcers in lower limbs and number of amputations were inconclusive. The outcomes of myocardial infarction, stroke and mortality were reduced with the use of clopidogrel and ticagrelor. Dual platelet inhibition with aspirin and clopidogrel reduced ischemic events, but with an increase in the rate of non-serious bleeding.